2008
DOI: 10.1002/ijc.23135
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor genotypes and colon cancer: Gene–gene and gene–lifestyle interactions

Abstract: Leptin may play an important role in colorectal cancer because of its role in energy balance, insulin and inflammation. We evaluated the LEP rs2167270 (19 G > A) and rs7799039 (22548 G > A) poly-morphisms and the leptin receptor, LEPR rs6588147 (located in intron 2), polymorphism with risk of developing colon cancer in a study of 1,567 cases and 1,965 controls. We evaluated the effects of the polymorphisms with body mass index (BMI), recent use of aspirin/NSAIDs and genetic variations in genes related to insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 46 publications
3
57
1
Order By: Relevance
“…Due to its mitogen effect, a condition of hyperleptinemia could favour the development of malignancies. In close agreement with this hypothesis, several lines of evidence support the role of leptin in the neoplastic processes [6][7][8][9]. Moreover, this is further supported by some genetic evidences showing a correlation between serum leptin levels, leptin receptor polymorphisms, and the risk of breast cancer [10,11].…”
supporting
confidence: 55%
“…Due to its mitogen effect, a condition of hyperleptinemia could favour the development of malignancies. In close agreement with this hypothesis, several lines of evidence support the role of leptin in the neoplastic processes [6][7][8][9]. Moreover, this is further supported by some genetic evidences showing a correlation between serum leptin levels, leptin receptor polymorphisms, and the risk of breast cancer [10,11].…”
supporting
confidence: 55%
“…In addition to the report about the relationship between the RETN SNP C-420G and the risk of CRC (17), only one study has addressed the question of an association between genetic variation in the adipokine genes and the risk of CRC (51). In that study, a decreased risk for the AA genotype carriers of the SNP rs2167270 in the 5 0 -UTR of the LEP gene was observed.…”
Section: Discussionmentioning
confidence: 97%
“…Of particular importance for cancer is the influence of leptin on suppressors of cytokine signaling 1 and 3 which in turn limits insulin signaling [49] . Although data directly linking leptin to colon cancer are limited, some studies have shown increased risk of colon and colorectal cancer with high serum leptin levels.…”
Section: Leptinmentioning
confidence: 99%